Assessing the Climate Security Sensitivity of WFP’s Foreign Policy Instrument Nexus Project in Tillaberi, Niger - Sarzana, Carolina; Ranaivo, Rondro; Cisse, Amadou; Mazunda, John; Läderach, Peter (2024)
This Info Note reports on the CSST case study application for the Foreign Policy Instrument (FPI) Nexus Project implemented in Tillaberi, Niger. It highlights the recommendations formulated by the CSST for the implementation of this project and the practitioners’ feedback on these results. The CSST analysis indicates the need to address shortcomings in the Building Institutions and Enhancing Knowledge mechanisms, while highlighting its significant peace co-benefits delivered through resource sustainability, social cohesion activities, and resilience building. Enhancing local knowledge integration in climate adaptation and environmental management could foster social cohesion and depoliticize common-pool resources, offering potential for increased intergroup contact. Moreover, recommendations include specific strategies for conflict management in resource access, as well as further collaborating with local governance to reform natural resource policies as a way to enhance regulation and promote inclusivity, resilience, and stability among groups.